Travma Sonrası Stres Bozukluğu Tanılı Ergene Bilişsel Davranışçı_x000D_ Yaklaşım: Bir Olgu Sunumu - PERDAHLI FİŞ, NEŞE (My University, 2019)
Çocuk ve ergen hastalarda travma sonrası stres bozukluğu tedavisi çok yönlü olup, hastaların yaşına ve özelliklerine uygun yöntemlerinseçilmesi ve tedavi sürecine aile üyelerinin katılımının sağlanması önemlidir. Travma odaklı bilişsel davranışçı terapinin etkinliği çocuk veergen hastalarda gösterilmiştir. Terapide psikoeğitim, maruz bırakma, tepki engelleme, davranışçı ve bilişsel müdahaleler, gevşeme egzersizlerive ev ödevleri kullanılmaktadır. Bu olgu sunumunda 15 yaşındaki erkek hastanın geçirdiği trafik kazası sonrası 1 yıllık bilişsel davranışçı terapisüreci tartışılmıştır.

The treatment of posttraumatic stress disorder in children and adolescents is multifaceted and it is important to select appropriate methods_x000D_ for the age and characteristics of patients and to ensure the participation of family members in the treatment process. Efficacy of traumafocused cognitive behavioral therapy has been demonstrated in children and adolescents. Psychoeducation, exposure, response prevention,_x000D_ behavioral and cognitive interventions, relaxation exercises and homework are used in therapy. In this case report, it was discussed 15-year-old_x000D_ male patient underwent 1-year cognitive behavioral therapy after a traffic accident.
Summary: Cognitive Behavioral Approach on an Adolescent Patient with Posttraumatic Stress Disorder: A Case Report